Outcome of First Trimester Pregnancy in Cases with Impending Embryonic Demise - Hend Hassan (Al-Azhar University, Faculty of Medicine (Damietta), 2020)
Background: Miscarriage is the most common adverse pregnancy outcome which has detrimental psychological consequences for the woman and her partner and delays successful childbearing. Normal embryonic heart rate is about [100-200] bpm at 5 weeks gestation then it increases progressively over the subsequent 2-3 weeks. Fetal demise often occurs within one week after the slow embryonic heart rate and always occurs by the end of the first trimester. Aim of the work: The aim of the present study was to investigate the relation between first trimester miscarriage and slow embryonic heart rate at sixth week of gestational age and other risk factors of miscarriage. Patients and methods: A prospective observational cohort study was conducted in the department of Obstetrics and Gynecology, Al-Azhar Faculty of medicine [Damietta] during the period from September 2017 to September 2018 on 90 pregnant women who had slow embryonic heart rate [80-100] bpm at sixth week of gestational age. All were submitted to full history taking, clinical and ultrasound examination and followed up till the end of their pregnancy and outcome was documented. Results: Percentage of aborted cases at the 8th week of gestational age was [38.9%], while, [20%] at the 10th week and [15.4 %] at 13th week. Whom fetus had a heart rate less than 90 were at risk 23.8 times for experiencing abortions more than other females. Conclusion: Slow embryonic heart rate is one of the earliest predictors for the first trimester fetal demise and it is one of the newest studies